First evaluation of the Behavioral Addiction Indoor Tanning Screener (BAITS) in a nationwide representative sample. (1st January 2018) - Diehl, K.; Görig, T.; Breitbart, E.W.; Greinert, R.; Hillhouse, J.J.; Stapleton, J.L.; Schneider, S.
Summary: Previous research showed that indoor tanning might have the potential to be addictive. Different screening instruments for indoor tanning addiction exist, however research shows that they are not all suitable for measuring a potential indoor tanning addiction. Due to that a new instrument, the Behavioral Addiction Indoor Tanning Screener (BAITS), was developed. This study from Germany aimed to find out whether the BAITS is an appropriate instrument for screening individuals with symptoms of a potential indoor tanning addiction. The study is based on data from the National Cancer Aid Monitoring on Sunbed Use (NCAM) consisting of cognitive interviews and a nationwide representative telephone survey. Statistical analysis showed that the BAITS seems to be a valid and reliable tool. Altogether, 19.7% of current and 1.8% of former tanning bed users screened positive for symptoms of a potential indoor tanning addiction. However, this is not a final diagnosis of indoor tanning addiction. A final diagnosis would require a more formal assessment. Nonetheless, the BAITS may help physicians and other health care providers to identify individuals in particular need of specific counselling in order to avoid the continuous use of tanning beds. In addition, it is easy to use in large surveys due to its short length and its easily answerable questions.